2005
DOI: 10.1111/j.1474-9726.2005.00154.x
|View full text |Cite|
|
Sign up to set email alerts
|

Complicating the role of p53 in aging

Abstract: Recently, we described a p53 mutant mouse model (p53+/m mouse model) that presented a paradox, in which tumor free survival was coupled to reduced lifespan instead of extended lifespan (Tyner et al ., 2002). The p53+/m mice expressed a truncated p53 transcript attached to a leader sequence and showed a moderate increase in p53 activity. Based on this data we hypothesized that enhanced levels of p53 caused the early aging and cancer resistance phenotypes. This hypothesis was attractive as it indirectly implied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…While we hypothesize that most of the cancer resistance and accelerated aging phenotypes can be explained primarily by effects of the M protein on wild-type p53 in the p53+/m mouse, the possibility remains that some or all of the phenotypes could be attributed to haploinsufficiency resulting from the 600 kb deletion upstream of the truncated p53 gene. In fact, there has been some controversy in the literature regarding this issue (Gentry and Venkatachalam, 2005;Vijg and Hasty, 2005). Several lines of evidence support our hypothesis that the cancer resistance and aging phenotypes are driven by chronic p53 hyperactivity in the p53+/m mouse.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…While we hypothesize that most of the cancer resistance and accelerated aging phenotypes can be explained primarily by effects of the M protein on wild-type p53 in the p53+/m mouse, the possibility remains that some or all of the phenotypes could be attributed to haploinsufficiency resulting from the 600 kb deletion upstream of the truncated p53 gene. In fact, there has been some controversy in the literature regarding this issue (Gentry and Venkatachalam, 2005;Vijg and Hasty, 2005). Several lines of evidence support our hypothesis that the cancer resistance and aging phenotypes are driven by chronic p53 hyperactivity in the p53+/m mouse.…”
Section: Discussionsupporting
confidence: 76%
“…Unfortunately, the nature of the serendipitously generated m allele mutation precluded a straightforward mechanistic interpretation. Exons 1−6 of the m allele are deleted, resulting in expression of a chimeric RNA message in which a leader sequence from a gene (Arhgef15) 600 kb upstream of p53 is fused to exons 7−11 of the p53 gene (Tyner et al, 2002;Gentry and Venkatachalam, 2005). This m message produces a truncated C-terminal p53 protein translationally initiated from an ATG codon in p53 exon 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, HSC number and proliferative potential have been shown to be decreased in p53 +/m mice and increased in late age haploinsufficient p53 +/− mice (Dumble et al, 2007). Unfortunately, the deletion leading to this truncation also causes haploinsufficiency in 23 nearby genes (Gentry and Venkatachalam, 2005). Although the potential synergistic effects of such a large deletion significantly complicates interpretation of these findings, the phenotypes observed in p53 +/m , p53 m/− , p53 +/− , and p53 −/− mice suggest that the premature aging phenotypes in p53 +/m mice are most likely related to the p53 truncation (Vijg and Hasty, 2005).…”
Section: Hyperactivation Of the P53 Pathway And Agingmentioning
confidence: 99%
“…p53 hyperactivation in these mice is accompanied by a B20% shorter median lifespan and the premature appearance of several age-related phenotypes, including osteoporosis, kyphosis, generalised organ atrophy, impaired wound healing, hair re-growth defects and slowed recovery following myeloablation. While it has been shown that the deletion leading to this truncation also causes haploinsufficient loss of 23 nearby genes (Gentry and Venkatachalam, 2005), a careful analysis of the phenotypes observed in p53 þ /m , p53 m/À p53 þ /À and p53 À/À mice suggests that the premature ageing phenotypes in p53 þ /m mice are most likely related to the p53 truncation (Vijg and Hasty, 2005). In addition, phenotypes consistent with those observed in p53 þ /m mice have been obtained by expressing a naturally occurring N-terminally truncated isoform of p53 called p44 (Maier et al, 2004).…”
Section: Tumour-suppressing Mechansims Degrade Tissue Renewal Capacitymentioning
confidence: 99%